2009
DOI: 10.1097/gme.0b013e31818c9306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menopause and hormone therapy on erythrocyte deformability

Abstract: These results indicate that erythrocyte deformability may worsen with the decrease in the estrogen level because of the onset of menopause, and also suggest that ET and EPT may allow it to recover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…An intriguing report indicated that female rats had greater mesenteric nitric oxide production than males suggesting potential biological underpinnings for gender-specific iNOS-EIBS relationship(39). Alternatively, estrogens have been shown to impact on micro-circulation (coronary) directly or through alterations in RBC deformity(40). Since most women who develop CRC are post-menopausal (hence minimal ovarian estrogen secretion), we need to be circumspect about speculation on the role of sex hormones in EIBS.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing report indicated that female rats had greater mesenteric nitric oxide production than males suggesting potential biological underpinnings for gender-specific iNOS-EIBS relationship(39). Alternatively, estrogens have been shown to impact on micro-circulation (coronary) directly or through alterations in RBC deformity(40). Since most women who develop CRC are post-menopausal (hence minimal ovarian estrogen secretion), we need to be circumspect about speculation on the role of sex hormones in EIBS.…”
Section: Discussionmentioning
confidence: 99%